2022
DOI: 10.1101/2022.12.15.520653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian clock factors regulate seed oil accumulation by promoting fatty acid synthesis in Arabidopsis

Abstract: The circadian clock regulates temporal metabolic activities, enabling organisms to adapt to cyclic environmental changes, but how it affects lipid metabolism in plants is poorly understood. Our previous finding showed that the central clock transcription factors LATE ELONGATED HYPOCOTYL (LHY) and CIRCADIAN CLOCK ASSOCIATED 1 (CCA1) increased seed oil contents. Here we investigated the molecular and metabolic mechanism underlying the LHY and CCA1 regulated oil accumulation. Triacylglycerol (TAG) accumulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The interplay between the clock and metabolism is expected to strengthen the function of both processes in organisms. Increasing evidence supports the clock regulation of plant lipid metabolism, including the recent findings that the core Arabidopsis clock morning regulators LHY/CCA1 enhance fatty acid biosynthesis and lipid accumulation (Kim et al, 2019, 2023). In contrast, the evening regulator TOC1 decreases lipid production (Makni et al, 2024).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The interplay between the clock and metabolism is expected to strengthen the function of both processes in organisms. Increasing evidence supports the clock regulation of plant lipid metabolism, including the recent findings that the core Arabidopsis clock morning regulators LHY/CCA1 enhance fatty acid biosynthesis and lipid accumulation (Kim et al, 2019, 2023). In contrast, the evening regulator TOC1 decreases lipid production (Makni et al, 2024).…”
Section: Discussionmentioning
confidence: 95%
“…Reciprocally, the circadian clock modulates lipid metabolism by regulating the expression of lipid metabolic genes, as evidenced by circadian profiles of the genes and oscillatory accumulation of some lipid metabolites, including PA, in plants (Maatta et al, 2012; Hsiao et al, 2014; Nakamura et al, 2014 a and b; Kim et al, 2019). Recently, we reported that LHY and CCA1 enhanced the expression of KASIII that encodes β-ketoacyl-ACP synthase III by directly binding to its promoter, and this binding was inhibited by PA (Kim et al, 2023). KASIII catalyzes the first condensation step in the biosynthetic pathway of fatty acids incorporated into myriad lipid species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding seed development as a complex mechanism involving intricate pathways implies that multiple factors may contribute to the formation of seed components. A recent study unraveled the direct role of circadian rhythm regulators in initiating fatty acid synthesis in Arabidopsis seeds (Kim et al, 2023), further underscoring the multifaceted nature of seed development.…”
Section: Discussionmentioning
confidence: 99%